Whey ou soro de leite em produtos lácteos: comportamento do consumidor e análise de rótulos - Scarabotto, Larissa (2022)
The new consumption patterns directly portray the affection for a healthy lifestyle and the greater demand for nutritious foods. Due to the quality of its proteins, whey has become a market trend, being a fundamental ingredient in the industry. In general, consumers are not aware of the presence of whey in the formulation of products and some have a certain aversion to such raw material. With this, this work evaluated the consumer's perception regarding the presence of whey in dairy products, through the application of an online questionnaire prepared via Google Forms. The affective acceptance test was performed to determine the consumer's sensory acceptance of a product that contains whey in its formulation, in blind and informed conditions. Labels of products with high protein content, which have ingredients with whey in their composition, were also analyzed. It was found that many consumers associate “whey” with a healthy and protein option, but when mentioning “soro de leite” there is a certain aversion to the product and many are unaware of its health benefits. Many have the understanding that “soro de leite” is obtained after cheese manufacturing, but few know the origin of whey. With this, the consumer points out that whey is rich in good quality proteins, but many do not have the same opinion for “soro de leite”. Upon learning about the presence of whey in the composition of a dairy product, the consumer tends to give lower marks to that product. The industry makes frequent use of whey or derivatives in the formulation of dairy products with “high protein content”, this is because whey has good quality proteins in its composition, however, when highlighting the presence of “soro de leite” as an ingredient, it is common to use the term “whey” on the label. This happens because the word “whey” is more accepted by consumers than “soro de leite”. It is necessary to inform the consumer about this product in order to boost the appreciation and consumption of whey.